AN ANALYSIS OF TRANSLATION PROCEDURES USED BY GOOGLE TRANSLATE IN TRANSLATING THE GRAMMATICAL HIERARCHY (A Case Study of English - Indonesian Translation) - Wibowo, Ichsan Mukti (2015)
The present research entitled An Analysis of Translation Procedures Used by Google Translate in Translating the Grammatical Hierarchies aims at analyzing the translation procedures and identifying the translation quality of Google Translate products. A qualitative method was used to analyze the research. In analyzing the data, the researcher refers to some theories of translation procedures proposed by Peter Newmark (1988), Vinay & Darbelnet (1995 in Fawcet,1997) and Larson (1984) and a number of theories of translation quality proposed by Larson (1984), Tytler (1907), Nida and Taber (1982), Tytler (1791 in Basnett, 2002), Massoud (1988 in Abdellah, 2002), and El Shafey (1985 in Abdellah, 2002). The results of data analysis shows that there are seven procedures found in Google Translate products: literal (99 items or 49,5%), couplets and triplets (69 items or 34,5%), transposition (16 items or 8%), transference/borrowing (7 items or 3,5%), paraphrase (5 items or 2,5%), synonymy (3 items or 1,5%), and naturalization (one item or 0,5%). The second finding shows that the translation products of Google Translate is good or acceptable in translating words. On the other hand, the translation quality of GT products was quite unacceptable or inappropriate in translating phrases, clauses and sentences because the meaning was not delivered properly and therefore before using GT to translate phrases, clauses, and sentences, the users have to recheck the results of translation. Based on percentages of acceptable translation (82,5%) and unacceptable (17,5%). In the words level, there are more acceptable items (50 items). In the phrases level, there are 42 acceptable items and 8 unacceptable items. In the clauses level, there are 41 acceptable items and 9 unacceptable items. In the sentences level, there are more unacceptable items (18 items) and 32 acceptable items. Furthemore, the total selected items are 200 items (50 words, 50 phrase, 50 clauses, and 50 sentences). The total acceptable items are 165 items from 200 items and unacceptable items are 35 items from 200 items. Keywords: Translation Procedures, Google Translate, The Grammatical Hierarchy Penelitian yang berjudunl Analisis Prosedur Penerjemahan oleh Google Translate dalam menerjemahkan tingkatan tata bahasa ini bertujuan menganalisis prosedur penerjemahan dan mengidentifikasikan kualitas hasil penerjemahan Google Translate. Metode penelitian kualitatif deskriptif digunakan dalam penelitian ini. Dalam menganalisi data, teori prosedur penerjemahan yang dikemukakan oleh Peter Newmark (1988), Vinay & Darbelnet (1995 in Fawcet,1997) and Larson (1984) dan kualitas penerjemahan dikemukakan oleh Larson (1984), Tytler (1907), Nida and Taber (1982), Tytler (1791 in Basnett, 2002), Massoud (1988 in Abdellah, 2002), and El Shafey (1985 in Abdellah, 2002). Hasil dari analisis data menunjukan ada tujuh prosedur ditemukan di hasil penerjemahan Google Translate :literal (99 item or 49,5%), couplets and triplets (69 item or 34,5%), transposition (16 item atau 8%), transference/borrowing (7 item atau 3,5%), paraphrase (5 item atau 2,5%), synonymy (3 item atau 1,5%), and naturalization (1 item atau 0,5%). Adapun temuan kedua memperlihatkan bahwa hasil penerjemahan Google Translate itu bagus dalam menerjemahkan kata. Disamping itu, kualitas penerjemahan Google Translate tidak baik dalam menerjemahkan frase, klausa dan kalimat karena arti nya tidak tersampaikan dengan baik dan jadi sebelum menggunakan Google Translate untuk menerjemahkan frase, klausa dan kalimat, pengguna Google Translate harus mengecek kembali hasil penerjemahannya. Berdasarkan persentase penerjemahan yang dapat diterima sebesar 82,5% dan yang tidak dapat diterima sebesar 17,5%. Pada level kata, terdapat banyak penerjemahan yang dapat diterima sebesar 50 item. Pada level frase, terdapat 42 penerjemahan yang dapat diterima dan 8 yang tidak dapat diterima. Pada level klausa, terdapat 41 penerjemahan yang dapat diterima dan 9 yang tidak dapat diterima. Pada level kalimat, terdapat 18 penejemahan yang tidak dapat dterima dan 32 yang dapat diterima. Jadi, jumlah sampel penelitian adalad 200 item (50 kata, 50 frase, 50 klausa dan 50 kalimat). Jumla penerjemahan yang dapat diterima adalah 165 item dari 200 item dan yang tidak dapat diterima sebesar 35 item dari 200 item. Kata Kunci: Prosedur Penerjemahan, Google Translate, Tahapan Tata Bahasa